Identification of a respiratory-type nitrate reductase and its role for survival of mycobacterium smegmatis in wayne model - Khan, Arshad; Sarkar, Dhiman (Microbial Pathogenesis, 2006)
Nitrate reductase (NR) is found to be expressed in certain mycobacterium sp. whose link with the development of persistence is yet to be resolved. The present study demonstrates the action of selective inhibitors on NR as well as in the survival of Mycobacterium smegmatis using Wayne's model. During gradual shift down to anaerobic stage in Wayne's model, conversion of nitrate to nitrite became apparent in M. smegmatis. More than 97 percent inhibition was observed for the conversion of nitrate to nitrite by azide (0.05 mM) and thiocyanate (20 mM) in both whole-cell as well as its cell-free lysate, respectively. Under identical condition, chlorate (20 mM) inhibited nitrate reduction by 67 and 10 percent, respectively. At these concentrations, neither of azide, thiocyanate nor chlorate had any significant effect on cell growth under aerobic condition. In Wayne's culture model, thiocyanate and chlorate inhibited the growth of M. smegmatis by almost 2 logs at the same concentrations whereas azide inhibited by almost 1.75 log when added at the time of inoculation. Exposure of same culture at 96 h after inoculation in Wayne's model to these inhibitors showed 1.74, 1.95 and 2.37 log inhibition of viable cells with respect to azide, thiocyanate and chlorate. These findings further indicated that NR inhibitors kill the bacilli at anaerobic stage under the experimental condition mentioned. Metronidazole (MTZ) (2 mM) and Nitrofurantoin (NIT) (0.3 mM) reduced the cell number at both stages by < 0.7log. They did not have any effect on NR. Altogether, the results clearly indicate that NR-specific inhibitors could become more promising in killing the bacilli at anaerobic stage than the available conventional drugs. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Mycobacterium smegmatis; nitrate reductase; Wayne model